Optimizing Savonius Wind Turbine Performance: Analysis of Blade Number's Influence - M. Rizky Ananda (IHSA Institute, 2024)
This research investigates the impact of blade number on the performance characteristics of Savonius wind turbines, shedding light on optimal design configurations and operational considerations. Through a combination of experimental testing and computational simulations, the study systematically analyzes key performance metrics including power output, torque generation, rotational speed, and efficiency across varying blade configurations. Findings reveal nuanced relationships between blade number and turbine performance, with implications for design optimization and operational adaptability. While turbines with a higher number of blades demonstrate advantages in terms of energy capture and torque production, they may also encounter challenges related to stability and efficiency. Conversely, turbines with fewer blades exhibit superior rotational dynamics and efficiency under certain conditions but may face limitations at higher wind speeds. The study underscores the importance of holistic optimization approaches that balance competing objectives and trade-offs in turbine design. Looking ahead, collaborative efforts between academia, industry, and government stakeholders are essential to drive innovation and realize the full potential of Savonius wind turbines as a viable, sustainable energy solution for a greener future.